Digital Humanities and Conspiracies of [Non]Reading - Дојчиновић, Биљана (Poznańskie Studia Slawistyczne, 2016)
The article tries to answer the following question: “what is the potential of digital data bases in research of the history and theory of marginal literatures”, that is, in the research of women’s writing? The focus of the text is on the data base Knjiženstvo, as well as on the complete project Knjiženstvo, theory and history of women’s writing in Serbian language until 1915 which connects its topic with European context in an innovative way.